Application of Urban Waste Organic Fertilizer on the Growth of Mustard Plants (Brassica Juncea L.) - Indriani Puspita Sari; Sri Hidayati; Nurlina; Mahrus Ali; Sri Purwanti (Agricultural Science, 2020)
Purpose of this study was to determine the effect of urban organic fertilizer and garden soil on the growth of mustard greens. Implementation at Experimental Garden Faculty of Agriculture, Merdeka University Surabaya Jl. Ketintang Madya VII / 2 Surabaya. This research method used a randomized block design (RAK), where the treatment used (1) factor, namely urban waste organic fertilizer consisting of 8 levels of treatment and repeated 3 times to obtain good results. The parameters of the observations carried out were observing plant length, number of leaves, plant wet weight, observations were made from the age of 14 DAS to 35 DAS with intervals of once a week. The results showed that the treatment of the effect of urban waste organic fertilizer on the growth of mustard greens can be concluded as follows: (1) There is a significant interaction in the treatment of organic fertilizers on the variable number of leaves aged 14 DAS and plant wet weight. The best results were shown in the treatment dose of 15% urban waste organic fertilizer and 85% soil (P3); (2) Treatment of urban waste organic fertilizer at a dose of 15% and soil 85% has a very significant effect on plant length growth at 14 DAS and plant wet weight at harvest and (3) Application of urban waste organic fertilizer with a composition of 15% and soil is 85%. The optimal dosage is able to bind nutrients and provide nutrients according to the needs of the mustard plant.